Use of FDA approved medications for Alzheimer's disease in mild dementia is associated with reduced informal costs of care. (21st March 2018) - Behrens, Stephanie; Rattinger, Gail B.; Schwartz, Sarah; Matyi, Joshua; Sanders, Chelsea; DeBerard, M. Scott; Lyketsos, Constantine G.; Tschanz, JoAnn T.
ABSTRACT: Background: The use of FDA approved medications for Alzheimer's disease [AD; FDAAMAD; (cholinesterase inhibitors and N-methyl-D-aspartate receptor antagonists)] has been associated with symptomatic benefit with a reduction in formal (paid services) and total costs of care (formal and informal costs). We examined the use of these medications and their association with informal costs in persons with dementia. Method: Two hundred eighty participants (53% female, 72% AD) from the longitudinal, population-based Dementia Progression Study in Cache County, Utah (USA) were followed up to ten years. Mean (SD) age at baseline was 85.6 (5.5) years. Informal costs (expressed in 2015 dollars) were calculated using the replacement cost method (hours of care multiplied by the median wage in Utah in the visit year) and adjusted for inflation using the Medical Consumer Price Index. Generalized Estimating Equations with a gamma log-link function were used to examine the longitudinal association between use of FDAAMAD and informal costs. Results: The daily informal cost for each participant at baseline ranged from 0 to 318.12, with the sample median of 9.40. Within the entire sample, use of FDAAMAD was not significantly associated with informal costs (expβ = 0.73, p = 0.060). In analyses restricted to participants with mild dementia at baseline ( N = 222), use of FDAAMAD was associated with 32% lower costs (expβ = 0.68, p = 0.038). Conclusions: Use of FDAAMAD was associated with lower informal care costs in those with mild dementia only.